A study on the use of propane (R-290) in vending machines as a substitute for R-134a to minimise the global warming potential. (2018) - Alkhaledi, Khaled A.; Means, Kenneth
The refrigerant R-134a is widely used in vending machines, and it is a greenhouse gas with high global warming potential. The United States Environmental Protection Agency has mandated that R-134a be replaced with an environmentally friendly refrigerant. In this study, we compared the performance and safety of R-290 as a substitute for R-134a in vending machines. We compared the two refrigerants in a vending machine equipped with a single-stage compressor, four thermocouples, and a data log recorder. Our results demonstrate that R-290 performs as well as R-134a; in addition, it uses 31.4% less energy and 60% less refrigerant. The evaporator and condenser temperatures for R-290 were comparable to those for R-134a. Therefore, we conclude that R-290 is an excellent replacement for R-134a. In addition, R-134a's global warming potential is 1300, while R-290's global warming potential is 3, and its ozone depletion potential is zero. Finally, R-290 can be used safely and complies with Underwriter Laboratory ® safety standards.